Pentingnya Ruang Ibu dan Anak sebagai Fasilitas Pendukung Kegiatan Menyusui di Area Publik - Ruki, Ulli Aulia (Bina Nusantara University, 2011)
A variety of interior now days have become diversly demand following on the customer needs as the visitor in the public space. Nowadays, department store start narrowing down its service facilities based on visitor needs such as children indoor playground, pray room, and nursery room. Nowdays mothers are aware of the importance to breastfeed exclusively their baby in their first six months; Breastfeeding is the new lifestyle. Nevertheless, there are only a few rooms that fully supported breastfeeding activity in public area. This journal will give the idea about a proper interior should be applied in the nursery room and the advantages of being supported to the breastfeeding activity for management mall or company who are providing the room as their services. Data are given by analysis and comparing the proper or deficient interior on several nursery rooms. In conclude, facilitating an appropriate, comfort and hygienist rooms for mother and baby are one of the approach to be acknowledged as the excellent services by the customer.